Ambulatory blood pressure monitoring profiles in Asia - Bambang Widyantoro; Jennifer M. Nailes; Apichard Sukonthasarn; Arieska Ann Soenarta; HOPE Asia Network (The Journal of Clinical Hypertension, 2024)
Abstract High blood pressure (BP) remains a major health problem globally, with a proportion of hypertension‐mediated organ damage (HMOD) increasing worldwide including in Asia region. Cardiovascular (CV), cerebral and kidney diseases related to hypertension were reported to be closely associated with morning surge and nocturnal hypertension—a subset of BP variability—which can be detected by out‐of‐office BP measurement. Ambulatory BP monitoring (ABPM) and Home BP monitoring (HBPM) have been recommended by major guidelines to be used in the evaluation of BP variability and outcomes’ prediction of hypertension patients. However, an interesting profile of ABPM in Asia has been reported and hypothesized to correlate with different outcomes. This review will focus on the current recommendation of ABPM use by the guidelines, the major different profiles of ABPM in Asia as compared to Western countries according to clinical indications, and the challenges in implementing optimal use of ABPM in Asian countries based on available evidence.